Surgical Anatomy Around the Orbit : the System of Zones. - Zide, Barry M. (Wolters Kluwer Health, 2005)
This full-color surgical atlas provides a detailed, true-to-life view of periorbital anatomy as seen during an operative procedure. More than 130 photographs of fresh cadaver dissections and more than 100 vivid drawings by an award-winning ophthalmic artist enable surgeons to thoroughly preview this complex anatomy prior to surgery. Using his popular concept of facial zones, Dr. Zide depicts the fine anatomic details necessary for today's advanced cosmetic and reconstructive procedures. A chapter on the seventh cranial nerve shows what tissue is innervated and delineates the exact zone of safe.